The degree of effectiveness of training programs for the employees of the Municipality of Asir Region - Al-Shahri, Turki Gharman Mohammed; Al-Zaidani, Turki Yahya Mohammed; Al-Shahri, Mohammed Ali Abdullah (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to know the degree of the training programs for Asir Municipality staff. This study depends on the descriptive survey method for 140 employees using three factors. These three factors are; the effectiveness of the programs, the obstacles to achieve them, and the ways to apply them.Accordingly, the result of the study shows that the reality of these programs appears at the middle level of the average of study tool. On the other hand, the estimation of the programs obstacles and implementation appear high.In conclusion, the study suggests some procedures and recommendations that needed to be considered for these training programs in order to achieve the goals.
Keywords: training; training programmes; effectiveness of training programmes